2014
DOI: 10.1104/pp.113.232389
|View full text |Cite
|
Sign up to set email alerts
|

Flavan-3-ols in Norway Spruce: Biosynthesis, Accumulation, and Function in Response to Attack by the Bark Beetle-Associated Fungus Ceratocystis polonica        

Abstract: Proanthocyanidins (PAs) are common polyphenolic polymers of plants found in foliage, fruit, bark, roots, rhizomes, and seed coats that consist of flavan-3-ol units such as 2,3-trans-(+)-catechin and 2,3-cis-(–)-epicatechin. Although the biosynthesis of flavan-3-ols has been studied in angiosperms, little is known about their biosynthesis and ecological roles in gymnosperms. In this study, the genes encoding leucoanthocyanidin reductase, a branch point enzyme involved in the biosynthesis of 2,3-trans-(+)-flavan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
123
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 61 publications
12
123
2
Order By: Relevance
“…The recovery of epicatechin after hydrolysis of PAs indicates that epicatechin might contribute to the extension of PA chains. Similar mechanisms also were observed in grape and Norway spruce (Bogs et al, 2005;Hammerbacher et al, 2014).…”
Section: Transcripts Of Flavan-3-ol Biosynthetic Genes Increase In Resupporting
confidence: 78%
See 3 more Smart Citations
“…The recovery of epicatechin after hydrolysis of PAs indicates that epicatechin might contribute to the extension of PA chains. Similar mechanisms also were observed in grape and Norway spruce (Bogs et al, 2005;Hammerbacher et al, 2014).…”
Section: Transcripts Of Flavan-3-ol Biosynthetic Genes Increase In Resupporting
confidence: 78%
“…Studies also demonstrated that the biosynthesis of flavan-3-ols and PAs increased after infection by fungal endophytes in poplar (Pfabel et al, 2012) as well as after infection by pathogenic fungi in other plant species, such as bilberry (Vaccinium myrtillus; Koskimäki et al, 2009) and Fagus crenata (Yamaji and Ichihara, 2012). Increased accumulation of flavan-3-ols also has been recorded in Norway spruce (Picea abies) during infection by necrotrophic fungi (Danielsson et al, 2011;Hammerbacher et al, 2014). Therefore, a range of plants, including poplar, respond to pathogen attack by accumulating both monomeric flavan-3-ols and PAs.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For the shikimate pathway and aromatic amino acid pathways (according to Maeda and Dudareva, 2012): ADH, arogenate dehydrogenase; ADT, arogenate dehydratase; CM, chorismate mutase; CS, chorismate synthase; DAHP synthase, 3-deoxy-D-arabino-heptulosonate 7-phosphate synthase; DHD-SDH, 3-dehydroquinate dehydratase-shikimate dehydrogenase; DHQS, 3-dehydroquinate synthase; EPSP synthase, 5-enolpyruvylshikimate 3-phosphate synthase; HPP-AT, 4-hydroxyphenylpyruvate aminotransferase; PDH, prephenate dehydrogenase; PDT, prephenate dehydratase; PPA-AT, prephenate aminotransferase; PPY-AT, phenylpyruvate aminotransferase; SK, shikimate kinase. For the flavonoid pathway (according to Hammerbacher et al, 2014): ANR, anthocyanidin reductase; ANS, anthocyanidin synthase; CHI, chalcone isomerase; CHS, chalcone synthase; DFR, dihydroflavonol 4-reductase; F3H, flavanone-3-hydroxylase; F39H, flavonol-39-hydroxylase; F395H, flavonol-39,59-hydroxylase; FLS, flavonol synthase; LAR, leucoanthocyanidin reductase. For the general phenylpropanoid pathway: CCoAOMT, caffeoyl-CoA 3-O-methyltransferase; C3H, p-coumaroyl shikimate 3-hydroxylase; C4H, cinnamate 4-hydroxylase; HCT, hydroxycinnamoyl-CoA shikimate/quinate hydroxycinnamoyl transferase; PAL, Phe ammonia lyase; 4CL, 4-coumarate-CoA ligase.…”
Section: A Broad Array Of Transcription Factor Families Were Induced mentioning
confidence: 99%